2021
DOI: 10.30867/action.v6i2.587
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan aktivitas fisik dan obesitas sentral dengan hiperglikemia wanita dewasa: Cross-sectional study

Abstract: Women in Indonesia are a group at risk of experiencing high blood glucose levels with increasing age. The purpose of the study was to analyze the relationship between physical activity and central obesity on hyperglycemia in adult women. The type of research is quantitative with a cross-sectional design on adult women at the Telaga Biru Public Health Center, Gorontalo Regency in 2019. The sample size is 248 people using purposive sampling. The method of collecting physical activity data is measured using a Phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Pada saat itulah energi meningkatkan sintesis lemak tubuh. Peningkatan lemak dalam tubuh dapat mempengaruhi terjadinya peningkatan lingkar pinggang (Bohari et al, 2021). Asupan SSB meningkatkan konsentrasi insulin di sirkulasi.…”
Section: Night Eating Syndrome Pola Tidur Dan Konsumsiunclassified
“…Pada saat itulah energi meningkatkan sintesis lemak tubuh. Peningkatan lemak dalam tubuh dapat mempengaruhi terjadinya peningkatan lingkar pinggang (Bohari et al, 2021). Asupan SSB meningkatkan konsentrasi insulin di sirkulasi.…”
Section: Night Eating Syndrome Pola Tidur Dan Konsumsiunclassified
“…Basic Health Research data from 2018 indicated a prevalence of 1.78% in women and 1.21% in men, while the 2013 data showed rates of 1.7% in women and 1.4% in men. In the last five years, the prevalence of hyperglycemia in women has increased, whereas it has decreased in men (Bohari et al, 2021). The overarching objective of this study was to discern the correlation between the occurrence of hyperglycemia and the duration of steroid therapy in patients with SLE at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia.…”
Section: Introductionmentioning
confidence: 99%